One‐ versus Two‐Electron Oxidation of Complexed Guanidino‐Functionalized Aromatic Compounds. Issue 35 (6th November 2014) - Trumm, Christine; Hübner, Olaf; Walter, Petra; Leingang, Simone; Wild, Ute; Kaifer, Elisabeth; Eberle, Benjamin; Himmel, Hans‐Jörg
Abstract: Herein, we report a rational synthetic access to dinuclear Cu II complexes with radical monocationic guanidine ligands. The starting point was the first directed synthesis of a dinuclear Cu II complex of the redox‐active, neutral guanidino‐functionalized aromatic (GFA) compound 1, 2, 4, 5‐tetrakis(tetramethylguanidino)benzene (1 ) as ligand by treatment of1 with Cu(OAc)2 . The neutral complex [1 Cu(OAc)2 2 ] was then oxidized with several oxidizing reagents. With I2 two‐electron oxidation occurred, thus leading to green salts of the dication [1 Cu(OAc)2 2 ] 2+ . In contrast, with AgPF6 or AgSbF6 one‐electron oxidation was observed to yield red salts of the monocation [1 Cu(OAc)2 2 ] +, which is a three‐spin system with one unpaired electron at each copper atom and at the ligand unit. Superconducting quantum interference device (SQUID) magnetometric measurements confirm a quartet electronic ground state that arises from strong ferromagnetic copper–ligand coupling. Intense charge‐transfer transitions in the visible region (576 and 536 nm) were observed in the electronic absorption spectra and assigned to strong ligand–ligand (1 · + ←OAc) charge‐transfer (LLCT) excitations. These LLCT bands open up the possibility of photoinduced redox reactions with [1 Cu(OAc)2 2 ] + driven by restoration of the aromatic system at the GFA ligand. Abstract : One‐electron oxidation of a neutral dicationic Cu II complex with a redox‐active guanidine ligand leads to red salts of the monocationic complex with a high‐spin (quartet) electronic ground state and strong ligand–ligand charge‐transfer transitions.